A temática atmosfera como ferramenta para o ensino de química - Wollmann, Ediane Machado (2013)
This paper shows a thematic approach and several actions which were developed in order to help in the process of teaching and learning Chemistry, as well as to contribute to the civic formation of the students from high school. It was developed, through the theme Atmosphere , teaching methodologies and activities which allowed the comprehension of the Chemistry contents in a contextualized way. This survey was applied to a sophomore group from a public high school in Restinga Seca, town located in the center of Rio Grande do Sul state. Before the actions were developed in the scholar environment, we analyzed three collections of Chemistry Textbooks (CT) which were chosen for being approved by PNLD 2012 and for being the most used by the teachers at the school where the study was applied. The results indicated that all the CT brought topics, contents and exercises related to the theme Atmosphere, differing among them on the approaching. On the first intervention in the school, we applied a questionnaire which allowed us to detect the perceptions of the students in relation to Chemistry, as well as their previous knowledge related to the theme Atmosphere . This analysis tool was the basis for the elaboration of the thematic workshops, allowing the delineation of the topics and contents to be addressed. With this information, we developed two thematic workshops with environmental concerns, Energy versus atmospheric pollution and Energy versus hydrosphere pollution, based on the Methodology of Problematization with the Arch of Charlez Maguerez. The data of this survey was collected through questionnaires, textual production, poster creation, folder creation, exercises, report elaboration and researcher journal, being those analyzed according to the Discursive Textual Analyses. Through the results found on this survey it is possible to conclude that the teaching of Chemistry was favoured by the thematic approach and by the methodologies applied on the interventions, for these actions helped on the association of chemical concepts to the daily life of the students, motivating them to learn.